2020
DOI: 10.1364/boe.379977
|View full text |Cite
|
Sign up to set email alerts
|

Automated diagnosis and segmentation of choroidal neovascularization in OCT angiography using deep learning

Abstract: Accurate identification and segmentation of choroidal neovascularization (CNV) is essential for the diagnosis and management of exudative age-related macular degeneration (AMD). Projection-resolved optical coherence tomographic angiography (PR-OCTA) enables both crosssectional and en face visualization of CNV. However, CNV identification and segmentation remains difficult even with PR-OCTA due to the presence of residual artifacts. In this paper, a fully automated CNV diagnosis and segmentation algorithm using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 49 publications
(49 reference statements)
0
35
0
Order By: Relevance
“…In vivo histological analysis using OCT scans is probably the most attractive method for studying the disease through artificial intelligence. In fact, these scans are rich in details and can be easily accessed by radiomics [37,38]. Moreover, structural OCT and OCT-A are amongst the most effective non-invasive imaging tools for several retinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo histological analysis using OCT scans is probably the most attractive method for studying the disease through artificial intelligence. In fact, these scans are rich in details and can be easily accessed by radiomics [37,38]. Moreover, structural OCT and OCT-A are amongst the most effective non-invasive imaging tools for several retinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, eyes with diabetic macular edema are frequently characterized by segmentation errors, as recently demonstrated by Ghasemi Falavarjani and colleagues [16]. A recent study using convolutional neural networks (CNNs) has demonstrated the utility of this algorithm to improve segmentation of OCTA data [17].…”
Section: Limitations and Artifactsmentioning
confidence: 94%
“…Many recent papers dealt with the contributions of artificial intelligence (AI) and deep learning (DL) approaches in ophthalmology [13][14][15]. However, only few works have addressed CNV screening on OCTA images using DL methods [16]. Most of the existing works focused on the diagnosis of AMD using OCT or Color Fundus Photography.…”
Section: Cnn Architecture and Transfer Learningmentioning
confidence: 99%
“…The obtained results showed an accuracy of 87.27% in differentiating healthy, no DR and DR eyes. In the same period, Wang et al [16] developed an algorithm based on two CNNs to classify input OCTA images (using structural volumes and enface retinal angiograms) as CNV or Non-CNV and then segment the CNV membrane when present. The proposed neural network included a cutoff threshold for CNV area to overcome the residual artifacts limitation that could be confounded with CNV.…”
Section: Cnn Architecture and Transfer Learningmentioning
confidence: 99%